Political Representation in Liquid Democracy - Valsangiacomo, Chiara (Frontiers in Political Science, 2021)
This article provides an in-depth survey of political representation in Liquid Democracy (LD). More precisely, it refutes two potential criticisms: 1) LD impoverishes the concept of political representation relative to existing representative democracies; 2) LD undermines the centrality of political parties. In answer to (1), the article shows that LD is compatible with a selection model of representation, in which proxies are characterized as gyroscopic representatives, driven by intrinsic motivation and indifferent to sanctions. This claim has far-reaching normative implications for the mandate-independence tradeoff, anti-elitism, and deliberation under LD. With regard to (2), the article examines the function of parties, arguing that, although it puts parties and interest groups on a level playing field, LD does not threaten partisanship, but rather expands the range of potential carriers of partisanship. In addressing these objections, this article demonstrates the democratic credentials of LD, showing that LD is compatible with a high-quality, democratic understanding of representation, which is surrounded by a cluster of thick concepts like commitment, intrinsic motivation, alignment of objectives, sympathy, trust, and dialogue. This turns LD into a powerful instrument for the refurbishment of representation both as a unique mode of political participation and as a practice of self-government.